Pelapisan benih melon (Cucumis melo L.) dengan ekstrak kulit jeruk untuk mempertahankan mutu fisiologis benih selama penyimpanan - Nurul Anisa; Florentina Kusmiyati; Karno Karno (Journal of Agro Complex, 2017)
The objective of this research was to study the effectiveness of orange peel extract as seed coating to mantain physiological quality of melon seed during 12 weeks storage. This research was conducted in Laboratory of plant physiology and breeding UNDIP, from December 2016 to April 2017. The research was assigned in completely randomized factorial design with the first factor was the storage periode (0, 4, 8 and 12 weeks) and second factor was the seed coating (control, CMC 1,5 %, orange peel extract (0,5 %, 1,0 %, 1,5 %, 2,0 %)). Interaction of storage period and seed coating showed significant affect to seed moisture content, seed germination and dry weight of normal seedling. Seed coating with orange peel extract 1,5 % was able to keep moisture content for 4 weeks, seed germination for 12 weeks and dry weight of normal seedling for 8 weeks. Keyword: melon, orange peel extract, physiological quality, seed storage